Predicting forest recreation benefits changes under different climate change scenarios - Hong-Wen Yu; Chun-Cheng Lin; Wan-Yu Liu (Trees, Forests and People, 2023)
Extreme climate and uncertainties in environmental changes have caused tourists to change their travel behaviors, and further affected the tourism value of tourism attractions. This study assessed the changes in the tourism value considering different climate change scenarios. Firstly, this study utilized meteorological data and number of tourists from the past decade to estimate the number of future tourists of 14 national forest parks in Taiwan. Questionnaire survey was conducted to investigate the travel durations of tourists; and the travel cost method was used to estimate the future tourism value. Then, the changes in the total value of each national forest park in Taiwan due to climate change were calculated. The results indicated that in national forest parks in Taiwan, the number of tourists and temperature increase were positively correlated, and the future tourism value decline because the recreation time in most national forest parks under climate change will decline. This study calculated the total changes in the future (from 2020 to 2100) tourism value of 14 national forest parks in Taiwan under climate change, and the maximum value reaches NT$183.473 billion. Under Scenario RCP 8.5, the tourism value is higher than that under Scenario RCP 2.6. Also, regarding time sequence, under Scenario RCP 8.5, the degree of decrease in tourism value in each area were smaller than those under Scenario RCP 2.6; in some areas, the tourism value increased. National forest park managers should promptly propose relevant adaptive policies to reduce the damage of climate change to tourism value.